Impact of Financial Development on Economic Growth in Nigeria - Emeka, Ikeh Frank; Yahaya, Ahmadu Salihu; Ali, Hamisu; Jaimu, Nekenneri Jerome (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This paper examined the impact of financial development on economic growth in Nigeria. The paper employed time series data (1985-2022) using ARDL approach, the objective of the study to access the causal relationship between financial development and economic growth in Nigeria. The data were obtained from Central Bank of Nigeria (CBN) and (WDI, 2023); Gross Domestic Product (GDP), Domestic Credit to Private Sector(DCRS), Market Capitalization (MACAP), Consumer Price Index (CPI), Foreign Direct Investment (FDI), Interest Rate (INTR) and Financial Development (FD) proxies by the ratio of broad money stock (M2). The study was anchored on Supply-Leading Hypothesis theory by Robinson 1952. The results show that all the indicators of financial development and its influence on economic growth, the DCRS has a negative influence on GDP, its impact is not statistically significant, implying an indirect effect, the CPI and FDI significantly affect GDP with CPI excreting a negative impact and FDI demonstrating a strong negative correlation. The ECM explores short term relationship among these variables and their implication for FD. Based on the following conclusion the following recommendations were made among others; strengthen price stability and implemented effective monetary policies and price control mechanism to maintain stable and controlled inflation.